2012
DOI: 10.1111/j.1095-8312.2012.01999.x
|View full text |Cite
|
Sign up to set email alerts
|

AFLP analysis shows high incongruence between genetic differentiation and morphology-based taxonomy in a widely distributed tortoise

Abstract: Morphology has traditionally been used to diagnose the taxa of various taxonomic ranks. However, there is growing evidence that morphology is not always able to reveal cryptic taxa, and that pronounced morphological variation could reflect phenotypic plasticity rather than evolutionary divergence. Spur‐thighed tortoises (the Testudo graeca complex), distributed in the western Palaearctic region, are characterized by high morphological variability and complicated taxonomy, which are under debate. Previous molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 63 publications
2
27
0
Order By: Relevance
“…Root length shortened by 80%. On the right, the correlation of mtDNA clades with AFLP groups (Mikulicek et al, 2013) and microsatellite clusters {K = 3, this study) is shown. Note that mtDNA clades A and E represent one and the same AFLP cluster, although they are not sister groups.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Root length shortened by 80%. On the right, the correlation of mtDNA clades with AFLP groups (Mikulicek et al, 2013) and microsatellite clusters {K = 3, this study) is shown. Note that mtDNA clades A and E represent one and the same AFLP cluster, although they are not sister groups.…”
Section: Introductionmentioning
confidence: 69%
“…Merging colours for microsatellite data symbolize admixed individuals. The letter C in the Caucasian AFLP group indicates the occurrence of a mitochondrial haplotype of clade C in a tortoise from Katekh, Azerbaijan, belonging to the Caucasian AFLP group (Mikulicek et al, 2013(Mikulicek et al, ). al., 2007.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…comm.). The taxon occurred in the geographic region now occupied by T. g. armeniaca (including its junior synonym, T. g. pallasi), as determined genetically Mashkaryan et al 2013;Mikulíček et al 2013), and may be ancestral to that or one of the other subspecies in the general Caucasus region, T. g. ibera or T. g. buxtoni. (Gmira 1993;Gmira et al 2013).…”
Section: ____stigmochelys Gray 1873cmentioning
confidence: 99%
“…This suggests, surprisingly, how often the evolution of genotype does not correspond to the evolution of phenotype. On the other hand, some species are phenotypically very variable but genetically more uniform (e.g., Testudo graeca: Fritz et al 2007;Mikulíček et al 2013; Natrix natrix: Kindler et al, 2013). However, different colorations in similar species can also reflect deep speciation processes (e.g., Dasypeltis: Trape et al, 2012).…”
mentioning
confidence: 99%